PENGARUH PEMBERIAN TEPUNG AZOLA (Azzola microphylla) FERMENTASI TERHADAP PERFORMA AYAM KUB (KAMPUNG UNGGUL BALITBANGTAN): EFFECT OF FERMENTED AZOLA FLOUR (Azzola miccrophylla) ON THE PERFORMANCE OF KUB CHICKENS (KAMPUNG UNGGUL BALITBANGTAN) - Mazarina, Nadiatul; Amran, Muhammad; Haryadi, Haryadi; Husna, Asmaul (Tropical Animal Science, 2025)
This study aims to determine the effect of fermented azola flour on the performance of KUB (Kampung Unggul IAARD) chickens. This study used 36 KUB chickens aged 4 weeks and were given a treatment ration of up to 4 weeks of maintenance. The research method used was an experimental method with a Complete Random Design (RAL), consisting of 4 treatments and 3 replicates. The therapy is the use of fermented Azolla in rations: A (Commercial Rations + 0% Azolla microphylla fermented in rations), B (Commercial Feed 512 + 5% Azolla microphylla fermented in rations), C (Commercial Feed 512 + 10% Azolla microphylla fermented in rations), and D (Commercial Feed 512 + 15% Azolla microphylla fermented in rations). The variables observed were body weight gain, ration consumption and ration conversion. The results showed that the treatment of fermented azola had an unreal different effect (P>0.05) on body weight gain, ration consumption and ration conversion. This study concludes that the addition of fermented azolla flour in the ration of KUB chickens up to 15% does not have a real effect on body weight gain, ration consumption and conversion of KUB chicken rations (Kampung Unggul Balitbangtan), which can be interpreted as the addition of azolla flour in the ration can replace commercial feed by 15%.